The Effect of using Word-Processing Software and Printed Material Towards Form Four Student’s Essay Writing on the Aspect of Achievement, Attitude and Writing Quality - Ayob, Adenan (2008)
The study attempts to compare the effects of using Word-Processing and conventional writing, based on pen, pencil and paper on essay writing by a group of form four students. The researcher conducted a quazi-experimental study using pre and post tests for the both experiment and control groups. The main focus of the study is to examine the students’ achievement in essay writing. The t-test was used to test the hypothesis of the study which was aimed at determining if there were any significant differences between students’ achievement using Word-Processing and pen, pencil and paper. The researcher also used text analysis design to determine the level of quality in the written product of student in the experimental and control groups. A text analysis form was used to record the quantity of words and the quality of ideas, language and sentence structures. Based on these criteria, the students’ achievement were graded as excellent, credit, good, average and minimum achievement in ideas, language and structural quality level. The outcome of the pre tests for both groups showed no significant difference in students’ achievement whether they were using Word-Processing or using pen, pencil and paper. Both groups achieved an average level of quality in writing that were graded as good and average. After the treatment was given to the experimental group, there were significant differences in the post tests and their scores in the quantity of words between the two groups. In the aspect of quality, the experimental group achieved excellent and credit levels. The control group achieved only good and average levels. The survey was also carried out to determine students’ attitudes towards Word-Processing and pen, pencil and paper. The t-test was also used to determine if there were any significant differences in students’ attitudes towards Word-Processing and conventional writing. The survey form was distributed to each student in both groups after the post test. The result showed that there were significant differences between students’ attitudes towards Word-Processing and those towards pen, pencil and paper in writing. The cost effectiveness study was also carried out to determine the cost effectiveness index in using Word-Processing and pen, pencil and paper. The result also indicated that the cost effectiveness index of Word-Processing was low compared to conventional writing based on pen, pencil and paper. Therefore, the result also showed that the cost effectiveness of Word-Processing was higher than that of pen, pencil and paper in writing. Based on the results, the cost effectiveness study is very important and should be implemented actively by the government in this new era of computer and information technology. From the result, it is the hope that the Malay Language teachers, including the management committee in schools should always carry out a comparative study between cost effectiveness in teaching and learning aids, and students’ achievement.